MIX2: A Novel Natural Multi-Component Modulator of Multidrug-Resistance and Hallmarks of Cancer Cells. (17th February 2019) - Gawel, Agata M.; Godlewska, Marlena; Grech-Baran, Marta; Stachurska, Anna; Gawel, Damian
Abstract: Multidrug resistance is one of the key barriers suppressing the effectiveness of drug therapies of malignant tumors. Here, we report a study on the effect of a mix of natural extracts (MIX2) prepared from fresh fruits of Prunus spinosa, Crataegus monogyna, Sorbus aucuparia, and Euonymus europaeus on the classic hallmarks of cancer cells and the expression of multidrug resistance proteins. In the studies, HeLa and T98G cell lines, and classic methods of molecular biology, including RT-qPCR, Western blot, flow cytometry, and confocal imaging, were used. Additionally, migration, adhesion, and proliferation assays were performed. The obtained results indicate that the MIX2 cocktail presents strong anti-cancer properties. MIX2 is not toxic, but at the same time significantly alters the migration, proliferation, and adhesion of tumor cells. Furthermore, it was found that cells exposed to the mixture presented a significantly reduced expression level of genes associated with MDR, including ABCB1, which encodes for glycoprotein P. In vitro data showed that MIX2 effectively sensitizes tumor cells to doxorubicin. We postulate that modulation of the multidrug resistance phenotype of tumors with the use of MIX2 may be considered as a safe and applicable tool in sustaining drug delivery therapies of malignancies.